Bayesian Chronological Modeling of SunWatch, a Fort Ancient Village in Dayton, Ohio. Issue 5 (2015) - Krus, Anthony M; Cook, Robert; Hamilton, Derek
Abstract : Radiocarbon results from houses, pits, and burials at the SunWatch site, Dayton, Ohio, are presented within an interpretative Bayesian statistical framework. The primary model incorporates dates from archaeological features in an unordered phase and uses charcoal outlier modeling (Bronk Ramsey 2009b) to account for issues of wood charcoal 14 C dates predating their context. The results of the primary model estimate occupation lasted for 1–245 yr ( 95% probability ), starting in cal AD 1175–1385 ( 95% probability ) and ending in cal AD 1330–1470 ( 95% probability ). An alternative model was created by placing the 14 C dates into two unordered phases corresponding with horizontal stratigraphic relationships or distinct groups of artifacts thought to be temporally diagnostic. The results of the alternative model further suggest that there is some temporal separation between Group 1 and Group 2, which seems more likely in the event of a multicomponent occupation. Overall, the modeling results provide chronology estimates for SunWatch that are more accurate and precise than that provided in earlier studies. While it is difficult to determine with certainty if SunWatch had a single-component or multicomponent occupation, it is clear that SunWatch's occupation lasted until the second half of the AD 1300s.